1994
DOI: 10.1093/bja/73.4.471
|View full text |Cite
|
Sign up to set email alerts
|

Spinal anaesthesia for Caesarean section: comparison of infusions of phenylephrine and ephedrine

Abstract: Maternal cardiovascular changes and neonatal acid-base status were assessed in 29 healthy women undergoing elective lower segment Caesarean section under spinal anaesthesia. The patients were allocated randomly to one of three groups to receive an i.v. infusion of one of the following: ephedrine 1 mg min-1 (group E1: n = 10), ephedrine 2 mg min-1 (group E2: n = 9), or phenylephrine 10 micrograms min-1 (group P: n = 10). Invasive arterial pressure was monitored continuously and if hypotension occurred (defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
81
1
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(89 citation statements)
references
References 0 publications
2
81
1
1
Order By: Relevance
“…Despite early reports suggesting that use of agonists was associated with adverse fetal effects 6,21 ; more recently performed comparative studies have shown that agonists are associated with better fetal acid-base status and maternal nausea and vomiting than ephedrine 2. Regarding phenylephrine, studies show that prophylactic phenylephrine infusion at LSCS is better than phenylephrine boluses to prevent hypotension during surgery. 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite early reports suggesting that use of agonists was associated with adverse fetal effects 6,21 ; more recently performed comparative studies have shown that agonists are associated with better fetal acid-base status and maternal nausea and vomiting than ephedrine 2. Regarding phenylephrine, studies show that prophylactic phenylephrine infusion at LSCS is better than phenylephrine boluses to prevent hypotension during surgery. 4 .…”
Section: Discussionmentioning
confidence: 99%
“…The total dose of phenylephrine given to patients in our study was greater than that reported in studies by other investigators [1,10,11]. However, our technique was based on our previous studies [2][3][4] in which we have not observed adverse neonatal effects despite similarly large doses of phenylephrine.…”
Section: Discussionmentioning
confidence: 78%
“…The incidence of hypotension during spinal anaesthesia and CSE varies depending on the definition and technique used and has been estimated to be as high as 80% [14] Most studies define hypotension as a mean SBP less than 20-30% of the baseline or an absolute systolic pressure of less than 90-100 mmHg. Adigun et al [8] defined hypotension as reduction in SBP >30% of baseline value.…”
Section: Discussionmentioning
confidence: 99%